The relationship between psychosocial distress and oral health status in patients with facial burns and mediation by oral health behaviour - Farooq Ahmad Chaudhary; Basaruddin Ahmad (BMC, 2021)
Abstract Background There is limited discussion on the influence of psychosocial factors on the oral health of patients with a facial burn injury. This report investigated the relationship between oral health and psychosocial distress in patients with facial burns and the role of oral health behaviour in mediating the relationship. Methods The data were part of a cross-sectional study that had systematically and randomly selected patients with > 10% total burn surface area from a burn centre in Pakistan. The oral health status (DMFT, CPI, OHI-S) and severity of facial disfigurement were assessed. Validated instruments in the Urdu language were self-administered and information relating to oral health behaviour (brushing and dental visits), oral health-related quality of life (OHIP-14), satisfaction with appearance, self-esteem, anxiety and depression, resilience, and social support were collected. The statistical analyses included simple linear regression, Pearson correlation, t-test, and ANOVA. Mediation analysis was carried out to examine the indirect effect by oral health behaviour. Results From a total of 271 participants, the majority had moderate to severe facial disfigurement (89%), low self-esteem (74.5%), and moderate to high levels of social support (95%). The level of satisfaction with appearance was low, whereas anxiety and depression were high. Disfigurement and satisfaction with appearance were associated with lower self-esteem and social support (p < 0.05). Greater severity of disfigurement, higher levels of anxiety and dissatisfaction with appearance, and lower levels of self-esteem and social support were associated with greater DMFT and OHIP-14 scores, worse periodontal and oral hygiene conditions, and less frequent tooth brushing and dental visits (p < 0.05). The main barriers to oral healthcare utilization were psychological and social issues (p < 0.05). The indirect effect by oral health behaviour was not significant for anxiety but was significant for disfigurement, satisfaction with appearance, self-esteem, and social support. Conclusion There is an association between the psychosocial factors and oral health of patients with facial burns through a direct effect and mediation by oral health behaviour.